The big book of reproducible graphic organizers : 50 great templates to help kids get more out of reading, writing, social studies, & more - Jacobson, Jennifer, 1958-; Raymer, Dottie, 1955- (Scholastic Professional Books, 1999)
"A collection of visual representations that provide students with successful methods of organizing, interpreting, and understanding material in Language Arts, Geography, History, Science, Mathematics, and study skills."
"All Grades"--Obálka
"These graphic organizers may be reproduced for classroom use."--Rub tit.l.
Keywords: vyučovací metody; aktivizační metody ve výuce; vyučovací předměty; jazyková výuka; zeměpis; dějepis; matematika; teaching methods; activisation methods in education; teaching school subjects; language teaching and learning; geography (school subject); history (school subject); mathematics; metodické příručky; šablony; methodological manuals; templates